Enamel hypoplasia in African enslaved individuals from Valle da Gafaria, Lagos, Portugal (15th–17th centuries) - Wasterlain, Sofia N. (2020)
Dental enamel hypoplasia, a defect of enamel formation, has been widely used for the investigation of growth disruptions in past populations, as it provides a permanent record of disturbances occurring during an individual's development. With the aim of recording changes in health status during development of the African enslaved individuals recovered from Valle da Gafaria, Lagos, Portugal (15th–17th centuries), linear enamel hypoplastic defects were investigated in a sample of 78 individuals aged 12–40+ years old. Of the 744 anterior teeth present, 13.0% were not observable due to dental calculus, tooth wear or intentional modifications. In all, 647 teeth were macroscopically observed for the presence of dental enamel defects. The position of each defect on the crown was scored by measuring its distance to the cemento‐enamel junction on the labial surface of the crown, being the age of occurrence of the physiological stress thereafter calculated. Of the 78 individuals, 89.7% had at least one defect. Of the 647 teeth, 63.5% presented at least one defect. The age of occurrence of the physiological stress ranged between 1.5 and 5.2 years of age, and the mean peak age was between 3.3 and 3.7 years. A previous study has found that the non‐adult individuals of this skeletal assemblage died more frequently between 7 and 9 years. Although these two age ranges may represent distinct sets of adverse factors, such as weaning and workload, respectively, they reinforce the idea that the Lagos's individuals experienced harsh living conditions during childhood.